2006
DOI: 10.1111/j.1365-2524.2006.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Self-help groups as mutual support: What do carers value?

Abstract: The literature suggests that the United Kingdom, in common with Europe, North America, Canada and Scandinavia, has seen significant growth in single-issue self-help/mutual aid groups concerned with health and social care issues since the 1970s, but there is only ad hoc academic and policy interest in such groups in the United Kingdom. This article presents findings from a doctoral study with two self-help/mutual aid groups for carers in South-East England. The data are drawn from semistructured interviews with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 11 publications
1
50
0
4
Order By: Relevance
“…Analysis revealed that it was the process of sharing and exchanging stories that made it possible for active members to share their coping strategies and to expose their difficulties (Munn-Giddings & McVicar, 2007). They found it difficult to expose their vulnerabilities even to sympathetic professionals and supportive family members were thought either not to fully understand the situation or had to be shielded from reality.…”
Section: Case 2: Carersmentioning
confidence: 99%
“…Analysis revealed that it was the process of sharing and exchanging stories that made it possible for active members to share their coping strategies and to expose their difficulties (Munn-Giddings & McVicar, 2007). They found it difficult to expose their vulnerabilities even to sympathetic professionals and supportive family members were thought either not to fully understand the situation or had to be shielded from reality.…”
Section: Case 2: Carersmentioning
confidence: 99%
“…Many individuals who attend peer-support groups tend to be characterised by a common trait -they have a tendency to relapse [38][39][40][41]. Hence they seek the on-going support and stability that the safe environment of a peer-support, self-help group provides [32,33].…”
Section: Limitations Of the Current Studymentioning
confidence: 99%
“…En el proceso de aprendizaje de los cuidadores, se reciben determinadas ayudas de apoyo e indicaciones desde la vivencia de otros familiares que han pasado por la misma situación. Encontramos el análisis de Munn-Giddings (2006) donde investiga la importancia que otorgan los cuidadores al pertenecer a grupos de autoayuda y los beneficios que obtienen.…”
Section: Buscando Ayuda En Las Asociacionesunclassified
“…Los cuidadores que acuden a estos grupos se sienten más seguros de sus conocimientos, destrezas y habilidades y en sus relaciones con los profesionales debido a las oportunidades que el grupo les brinda para hablar sobre su situación y obtener diferentes perspectivas sobre el cuidar (Munn-Giddings, 2006). Según un estudio sobre programas de apoyo grupal encontró que a algunos cuidadores el participar de estos grupos de apoyo les había posibilitado no sólo aceptar su condición como cuidadores, sino informarse y aprender los asuntos fundamentales sobre la demencia y su cuidado (Biurrun, 20003).…”
Section: Buscando Ayuda En Las Asociacionesunclassified